On the entropy generation and exergy loss of laminar premixed flame under engine-relevant conditions. (1st January 2021) - Liu, Daojian; Wang, Hu; Zhang, Yan; Liu, Haifeng; Zheng, Zunqing; Yao, Mingfa
Highlights: The first to analyze entropy generation characteristics of hybrid deflagration/autoignition flame regime. When the transition of flame regime occurs, the entropy generation becomes dominated by chemical reactions. A new reaction pathway analysis method was proposed. Abstract: Analysis of entropy generation and exergy loss is effective and essential in evaluating the fuel efficiency in next-generation internal combustion (IC) engines that are expected to operate at higher pressures. At such conditions, the hybrid deflagration/autoignition flame structures may exist during the combustion process. However, currently, most of the studies on entropy generation of laminar premixed flame are performed for mixtures at normal temperatures and pressures, under which the flame is stabilized by heat and mass transfer. This study compares the entropy generation and exergy loss characteristics when the transition of regime under engine-relevant conditions occurs, which is identified based on the ratio of the corresponding flame to homogeneous ignition time scales. The results indicate that when the transition from flame propagation to autoignition front occurs, the entropy generation and exergy destruction sources from heat and species mass transfer vanish and become dominated by chemical reactions. The total entropy generation from chemical reaction increases due to the larger flame thickness and variations in fuel consumption pathway. The reaction pathway analysis reveals that for the flame stabilized by autoignition with initial temperature located in the region of low-temperature and negative temperature coefficient chemistry, a great part of the entropy generation is produced by the low-temperature pathway, with the maximum flux ratio over 60%. Thus, more attention should be paid on the optimization of fuel consumption pathways to minimize the combustion irreversibility.